Two economic perspectives on the IPv6 transition - Dell, Peter (Camford Publishing Ltd, 2010)
Purpose – IPv6 is the replacement for the Internet’s incumbent protocol, IPv4. IPv6 adoption is required to allow the Internet to continue to grow; however, there has been almost no uptake since its standardisation in the late 1990s. This paper seeks to explain how this non-adoption may be a consequence of current policies paradoxically intended to promote IPv6. Design/methodology/approach – Economic theories of exhaustible resources and permit markets are used to provide an explanation for the lack of adoption of IPv6. Findings – The current policy approach will not yield a significant adoption of IPv6 until after the IPv4 address space is exhausted and may also constrain Internet growth after IPv4 exhaustion occurs. Practical implications – Current policies intended to promote IPv6 diffusion through the Internet must be reconsidered. The economics of permit markets in particular can inform discussions about IPv4 address transfer markets. Originality/value – Economic analyses of IPv6 adoption are almost non-existent and very few prior studies are known. This paper helps to rectify this important gap in the literature.